THE ROLE OF SOCIAL SUPPORT ON RESILIENCE IN PEOPLE LIVING WITH HIV AIDS: A SYSTEMATIC LITERATURE REVIEW - Gusni Rahma; Lenny Utama Afriyenti (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
People Living with HIV/AIDS (PLWHA) face multiple psychosocial challenges, including stigma, discrimination, and mental health problems that may reduce quality of life and treatment adherence. Resilience and psychosocial support are recognized as important protective factors that help PLWHA adapt positively to these challenges; however, existing evidence remains fragmented and has not been comprehensively synthesized. This study aimed to examine the role of psychosocial support in strengthening resilience and its implications for mental health among PLWHA through a systematic review approach. A comprehensive literature search was conducted across national and international scientific databases, including quantitative, qualitative, and review studies that addressed resilience, psychosocial support, and mental health among PLWHA, with a particular focus on Asian settings. Articles were selected based on predefined inclusion and exclusion criteria. The findings indicate that psychosocial support—such as support from family, peers, and healthcare providers—plays a significant role in enhancing resilience among PLWHA. Higher levels of resilience are consistently associated with lower levels of depression and anxiety, as well as improved psychological well-being and quality of life. In conclusion, psychosocial support is essential in strengthening resilience and promoting mental health among PLWHA, highlighting the importance of integrating psychosocial interventions into HIV/AIDS care services to support long-term well-being and adaptive coping.